PERAN RISIKO KREDIT DALAM MEMODERASI PENGARUH KECUKUPAN MODAL, PENYALURAN KREDIT DAN BOPO TERHADAP PROFITABILITAS - Warnayanti, Komang Ayu; Dewi, Sayu Ketut Sutrisna (E-Jurnal Manajemen; Vol 7 No 1 (2018)DO - 10.24843/EJMUNUD.2018.v7.i01.p05, 2018)
ABSTRACK Profitability is the company’s ability in generating profit. This study is aimed at determining the role of credit risk in moderating the influences of capital adequacy, credit channel, and Operational Expenses   to  Operating Income   ( BOPO) on profitability. The research was conducted on banking companies listed on the Indonesia Stock Exchange (IDX) period 2012-2014. The purposive sampling technique is used to determine sample and the number of selected samples is 35 banks. Data analysis technique used in this study is Moderated Regression Model. The results of this study show that capital adequacy has a positive impact; however, it is not significant on profitability. Credit channel has no significant negative impact on profitability. BOPO has a significant negative impact on profitability. Credit risk has the significant positive impact to profitability. It weakens the influence of BOPO on profitability and it is not able to moderate the influence of capital adequacy and credit channel to profitability.   Keywords: profitability, capital adequacy, credit channel, bopo, credit risk.